Role-taking in two micro-community sign languages: Phylogenetic insights - Martinod, Emmanuella (Frontiers in Communication, 2022)
This study aimed to examine the use of role-taking constructions in two micro-community sign languages (SLs): Yucatec Maya SL (YMSL), and Soure SL. Various role-taking types were quantified and changes in gaze direction were annotated on data regarding these two SLs. The results showed (i) a greater diversity of role-taking produced in YMSL, including complex role-taking (i.e., multiple perspectives or role-taking produced alongside lexical units), and (ii) changes in gaze direction before and after the production of role-taking constructions in both SLs. First, this suggests a phylogenetic development between the two SLs partly observable from the study of role-taking through the conceptual lens of bifurcation of the signer's intent. More broadly, an analysis of the phylogenesis of SLs would benefit from this kind of examination using analytical concepts relevant to SLs. Second, results seem to indicate that the phylogenesis of SLs would share similarities with the ontogenesis of SLs. Indeed, the less socially integrated and analyzed SL (Soure SL) displayed a less advanced degree of bifurcation since few complex role-taking constructions were observed. This is in line with the way these structures are acquired late by SL learners. Further studies on other micro-community SLs would be needed to validate the results of this study.